Long term outcomes of drug-coated balloons versus drug-eluting stents in patients with small vessel coronary artery disease - Hesham Refaat; Mohamed Arab (Indian Heart Journal)
Objective: Drug-eluting stents (DES) are a normative care of coronary stenosis. However, their efficacy was limited by stent thrombosis and in-stent restenosis especially in small vessel coronary artery disease (SvCAD). The aim of this study was to assess angiographic efficacy and clinical outcomes of drug coated balloons (DCB) as compared with DES in SvCAD setting. Methods: A total of 100 SvCAD patients with percutaeous angioplasty of culprit coronary arteries <3 mm diameter and >70 % stenosis were enrolled in this study. The patients were categorized into DES arm and DCB arm. One year clinical outcomes were assessed. The primary endpoint was in-lesion late lumen loss (LLL). The secondary endpoints were vessel thrombosis, major bleeding, all-cause death and major adverse cardiac events (MACEs). Results: One year clinical follow-up revealed that in-lesion LLL was significantly lower in DCB arm as compared with DES arm (p = 0.004). Composite MACE was significantly higher in DES group compared to DCB group (p < 0.001). Non-fatal myocardial infarction (MI), target lesion revascularization (TLR), and major bleeding in DES group were significantly higher than DCB group (p = 0.04 & p < 0.001 & p = 0.03, respectively). However, there was a numerically; but not significantly, higher incidence of cardiac death (p = 0.65), and vessel thrombosis (p = 0.18) in DES arm compared to DES arm. Conclusion: In SvCAD setting, DCB has favourable angiographic and clinical outcomes; as evidenced by lower LLL and composite MACE at one year follow up, compared to DES.